Representação política e filiação partidária: um diálogo transconstitucional à luz da Convenção Americana sobre Direitos Humanos - Costa Filho, Antonio Eudes Nunes da (2020)
The Constitution of the Federative Republic of Brazil establishes the need for political-party affiliation as a condition of citizens eligibility in the representative system (article 14, paragraph 3, V). For its part, the American Convention on Human Rights (ACHR) does not establish political-party affiliation to political candidacies in the representative system as a necessary requirement (art. 23). Thus, the research aims to examine the possibility of cognitive-dialogical opening between the Brazilian constitutional norms and the ACHR rules regarding the legal category of political-party affiliation. It is based on the assumption that the representative political-party model uses, based on Niklas Luhmann’s theory of selfproducing, self-referring and reflective systems, of the method of political elections to maintain the circularity of the political system through a potential legitimacy conferred to the elected representatives. However, in Brazil, with the constitutional monopoly of candidacies through the Political Parties, traditional populations, which have their own cultures and customs, are excluded from this representative system, generating complexity and breaks in the circularity of the political-constitutional system in heterogeneous society of Brazil. The research presents the following problem: it is possible to have a cognitive-dialogical opening between the original brazilian constitutional norm and the international norms of the ACHR regarding political-party affiliation for the purpose of including traditional populations, according to their customs and traditions, in the political-representative system of Brazil? That is because the law, when communicating through language, allows linguistic codes to be changed with the fixation of meanings to promote the reduction of social expectations and, in consequence, generate congruence and circularity in the political system in a heterogeneous society. The research uses the systemic approach method, and research technique with the bibliographic analysis, and categorical analysis of the Brazilian political-partys statutes and the cases in which the Inter-American Court interprets the article 23 of the ACHR.